Saujana Impian Nursery and Landscape / Shahrul Reza Ibrahim ... [et.al] - Ibrahim, Shahrul Reza; Abu Zarim, Azli; Mohtar, Mahathir; Jalani, Sasila; Yahya, Norfardina; Ghazali, Nida Hidayati (Faculty of Information Management, 2004)
After a long discussion about selecting the right name for our company, all the partnerships have agreed to choose Saujana Impian Nursery and Landscape. Saujana Impian Nursery and Landscape can be look as a good business because there is less company that provides landscaping service and most of them usually provide nursery only. Besides that, there is not much business that is related to nursery and landscape.